Effects of dietary macronutrients and body composition on glucose homeostasis in mice. Issue 1 (6th August 2020) - Hu, Sumei; Togo, Jacques; Wang, Lu; Wu, Yingga; Yang, Dengbao; Xu, Yanchao; Li, Li; Li, Baoguo; Li, Min; Li, Jianbo; Wang, Guanlin; Zhang, Xueying; et al.
Abstract: As a major health issue, obesity is linked with elevated risk of type 2 diabetes. However, whether disrupted glucose homeostasis is due to altered body composition alone, or whether dietary macronutrients play an additional role, independent of their impact on body composition, remains unclear. We investigated the associations between macronutrients, body composition, blood hormones and glucose homeostasis. We fed C57BL/6N mice 29 different diets with variable macronutrients for 12 weeks. After 10 weeks, intraperitoneal glucose tolerance tests were performed. Generalized linear models were generated to evaluate the impacts of macronutrients, body composition and blood hormones on glucose homeostasis. The area under the glucose curve (AUC) was strongly associated with body fat mass, but not dietary macronutrients. AUC was significantly associated with fasting insulin levels. Six genes from transcriptomic analysis of epididymal white adipose tissue and subcutaneous white adipose tissue were significantly associated with AUC. These genes may encode secreted proteins that play important previously unanticipated roles in glucose homeostasis. Abstract : Hu et al. found that disrupted glucose homeostasis in obese mice is mainly due to high body fatness, and dietary fat plays an additional role on fasting glucose levels.